"It is like living in a diminishing world": older persons' experiences of living with long-term health problems – prior to the STRENGTH intervention. Issue 1 (1st January 2020) - Åberg, Cecilia; Gillsjö, Catharina; Hallgren, Jenny; Berglund, Mia
ABSTRACT: Introduction : Ageing is often associated with multiple long-term health problems influencing older persons' well-being in daily living. It is not unusual that the point of interest in research is often on the management of the actual health problem instead of being holistic and person-centred. Purpose : To describe the phenomenon of living with long-term health problems that influence daily living, from the older persons' perspective. Methods : Qualitative individual interviews were conducted with 34 older persons living with long-term health problems. The data were analysed using a Reflected Lifeworld Research (RLR) approach, grounded in phenomenology. Results: Life with long-term health problems entails living in a diminishing world. It entails living in uncertainty, not being able to trust one's own ability. The freedom to make decisions of your own is deprived by relatives and health-care providers. Living with long-term health problems entails being dependent on support in daily life and a strive to maintain meaningfulness in daily living. Conclusions : The results address a need for extended individual and holistic guidance and support in living with long-term health problems to increase the older person's sense of well-being and meaning in life.